Evaluation of Renal Anionic Secretion Following Living-donor and Deceased-donor Renal Transplantation: A Clinical Pharmacokinetic Study of Cefoxitin Microdosing. Issue 6 (June 2020) - Kalluri, Hari V.; Sood, Puneet; Zhao, Wenchen; Randhawa, Parmjeet S.; Tevar, Amit D.; Hariharan, Sundaram; Humar, Abhinav; Venkataramanan, Raman
Abstract : Background: Renal transplantation is the treatment of choice for patients with end-stage renal disease. Because kidneys are the primary excretory organs for various drugs/drug metabolites, changes in renal graft function would significantly alter the clearance and exposure of renally secreted drugs. Renal allografts from living and deceased donors normally undergo numerous insults, including injuries associated with prolonged cold ischemic time, reperfusion, and nephrotoxicity due to calcineurin inhibitors. These physiologic and pharmacologic stresses can alter the expression and functional capacity of renal organic anionic transporters (OATs). Methods: The objectives of this study were to assess the longitudinal changes in renal anionic secretion in kidney transplant patients, to study the effect of prolonged cold ischemic time on OAT secretion in kidney transplant patients (living- versus deceased-donor recipients), and to compare OAT secretory capacity of renal transplant recipients with healthy volunteers. Cefoxitin was used as a probe drug to assess OAT secretion. Cefoxitin pharmacokinetics was studied in 15 de novo renal transplant recipients following intravenous administration of 200 mg cefoxitin within 14 d and beyond 90 d posttransplantation. Results: No longitudinal changes in real OAT secretion in early posttransplant period were observed, and there were no differences in renal OAT secretion between living- and deceased-donor renal transplant recipients. Overall, cefoxitin exposure was 2.6-fold higher and half-life increased by 2.2-fold in renal transplant recipients when compared with historical healthy controls. Conclusions: These results suggest that OAT system is functioning well, but renal transplant recipients would need significantly lower dosage of drugs that are primarily secreted via the OAT system compared with normal subjects.